ADIK PKL ABG SEBUAH MODEL PEMBELAJARAN ACTIVE LEARNING - Firdos Mujahidin (JENTRE, 2021)
The purpose of this research is The purpose of this research is to develop existing model, method, and approach into a new learning model as a series of activities, and it has been commonly practiced in learning. The research method used is Research and Development (R&D) designed by Richey and Klien at the 3rd level. The results showed that the learning model named "ADIK PKL ABG" can be applied in learning and successfully managed learning in an effective way. The name may have less positive perception in the future, so more positive and elegant acronym is in search